2019
DOI: 10.1016/j.ijscr.2019.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Ingested metallic foreign body impacted in the vermiform appendix presenting as acute appendicitis: Case report

Abstract: Highlights Foreign body appendicitis in children may be caused by a variety of ingested foreign bodies. Pins are the most common cause of foreign body appendicitis. The reported incidence of bowel perforation is less than 1%, especially with sharp, thin, pointed or long objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…There is a term used in some articles called (irreversible appendicitis), which indicates either gangrenous or perforated appendicitis, indicating that both cases are very di cult to be cured with conservative treatment and need surgical intervention. [1,5,8,9] Most series the rate of the complicated appendicitis is reported to be between 20-30% of the cases, in our study the rate of complicated appendicitis was 23.37%. Complicated appendicitis is found to be reported in higher age groups, in our study about 82.6% of the patients were below 30 years, and the correlation was not signi cant between the age and the complicated type (P value 1.00).…”
Section: Discussionsupporting
confidence: 56%
“…There is a term used in some articles called (irreversible appendicitis), which indicates either gangrenous or perforated appendicitis, indicating that both cases are very di cult to be cured with conservative treatment and need surgical intervention. [1,5,8,9] Most series the rate of the complicated appendicitis is reported to be between 20-30% of the cases, in our study the rate of complicated appendicitis was 23.37%. Complicated appendicitis is found to be reported in higher age groups, in our study about 82.6% of the patients were below 30 years, and the correlation was not signi cant between the age and the complicated type (P value 1.00).…”
Section: Discussionsupporting
confidence: 56%
“…Impaction of swallowed items might occur near areas of anatomical narrowing such as the lower esophageal sphincter, pylorus, ileocecal valve and, in rare instances, the appendiceal lumen [ 10 ]. Mohammed et al reported a case of screw ingestion in a 4-year-old boy, which was impacted in the appendiceal wall and thus resulted in acute appendicitis [ 11 ]. Plain radiograph (anteroposterior and lateral views) can reveal the presence of the foreign body and localizes its position within the gastrointestinal tract, therefore, is usually the initial radiological modality to utilize.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 5 years (2015 to time of publishing) there have been 13 cases of acute appendicitis secondary to foreign body ingestion reported in the literature [7] , [8] , [9] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . These included 8 men, 2 women and 3 children whilst the average age was 33.6.…”
Section: Discussionmentioning
confidence: 99%